BPZ inhibits early mouse embryonic development by disrupting maternal-to-zygotic transition and mitochondrial function - Zhiming Ding; Huilei Chen; Huiru Cheng; Caiyun Wu; Hongzhen Ruan; Bingjing Zhu; Ping Zhou; Zuying Xu; Huifen Xiang (Ecotoxicology and Environmental Safety)
The use of Bisphenol A (BPA) has been widely restricted due to its adverse health effects. Bisphenol Z (BPZ) is used as an alternative to BPA, and humans are widely exposed to BPZ through various routes. Recent studies have shown that BPZ exposure adversely affects mouse oocyte meiotic maturation. This study investigates the impact of BPZ exposure on early mouse embryonic development alongside an exploration of the underlying mechanisms. The findings reveal that exposure to BPZ leads to a reduction in early embryo quality and hinders developmental progression. RNA sequencing analysis has identified 593 differentially expressed genes as a result of BPZ exposure, highlighting considerable changes in early embryonic gene expression. Mechanistically, BPZ exposure inhibits the activation of the zygotic genome and impedes maternal mRNA degradation, thereby interfering with maternal-to-zygotic transition (MZT). Further analysis indicates compromised mitochondrial function, as evidenced by abnormal distribution, diminished membrane potential, and lower ATP levels. Consequently, BPZ-exposed embryos exhibit elevated levels of reactive oxygen species, superoxide anions, and oxidative DNA damage. Moreover, BPZ exposure is associated with an increase in γ-H2A.X expression. Additionally, BPZ exposure alters the expression levels of histone modifications, including H3K27me2, H3K27me3, H3K9me3, and H3K27ac, in early embryos. Collectively, BPZ exposure significantly impairs early embryo quality by disrupting mitochondrial function, inducing oxidative stress and DNA damage, altering histone modifications, and inhibiting MZT, ultimately resulting in hindered blastocyst formation. These findings underscore the profound adverse effects of BPZ on early embryonic development, indicating the need for caution when considering it as a safe alternative to BPA.